ANALISIS PSIKOLOGI SASTRA TERHADAP RAPE TRAUMA SYNDROME PELAKU UTAMA NASKAH DRAMA DEATH & THE MAIDEN KARYA ARIEL DORFMAN SEBAGAI ALTERNATIF REFERENSI BAHAN AJAR KELAS XI SMA - Juliana Fajar Firdaus; Panca Pertiwi Hidayati; Setiawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Literature is a work that not only provides entertainment, but also teaches the values of life. In addition to being full of beauty that can be enjoyed, a literary work must contain wisdom that can be interpreted. Literature can be a learning space for those who enjoy it. that way, literature is also related to education. In practice at school, literature learning is still full of obstacles. The majority of literature learning in schools is still theoretical, focusing only on the text, not the value of its content. One of the literary works that can be enjoyed is drama. In drama stories there are lessons about the reality of life that can be interpreted by students in schools. Especially the values that can stimulate the sensitivity of students about morals and social life. This research was conducted to analyze the Rape Trauma Syndrome of the main character of the play "Death and the Maiden" by Ariel Dorfman, as a representation of victims of sexual violence. The existence of this research aims to analyze what is the context of trauma symptoms that target the psyche of victims of sexual violence, how the mental form of the victim, and how the victim's personality structure is viewed from a psychoanalytic perspective. In this research, the author uses descriptive qualitative method, with literary psychology as the approach. From the results of the research, 9 contexts of Rape Trauma Syndrome symptoms were found in the drama script which were divided into acute and reorganization symptoms. In addition, there are 9 trauma symptoms shown by the main character, which are divided into Hyperarousal, Intrusive, and Numbing symptoms. Regarding the personality structure, 22 data were found, divided into 10 Id, 7 Ego, and 5 Super Ego. The results of the analysis will be used as an alternative reference for drama teaching materials for class XI high school.